Guerra en las aulas : violencia política contra los sindicatos del sector de la educación en Colombia (2009)
This article shows the research results about the political violence against teachers, not only does it introduce figures but also it goes into detail about the nature and the dynamics of the manner how teachers are affected by the political violence in Colombia. As well, it presents the different strategies of resistance that trade unionists in the educational sector and their allies, have developed throughout the years, in order to defend their human rights. The result of this research shows the conclusions about the current situation of the Colombian teachers and poses some suggestions, addressed to the international educational community, trade unions, human rights movement, on how to help our colleagues in Colombia